The Impact of Motivation Towards Employees Turnover at Pt. Sumatra Raya Sari Medan - Felix Leonardi; Sri Aprianti Tarigan; Elyzabeth Wijaya; Susanto; Benny Lim (Universitas Muhammadiyah Palu, 2026)
There are many kinds of motivation that manager can give to the employees. Not every employee are motivated by money, some are being motivated by other non financial motivation, such as facility, working hours, working environment. Due to the concept of law of individual differences, different people react to different incentives in different way. This means that people differ in personality, ability, values, and needs, and these differences manifest themselves in different reactions. Based on company sources, the last few months many employees who resigned from the job, and have not even had time to replace the company's employees who perform this turnover, some employees who still work also shows that there are indications the same, namely a desire to resign or get out of a job. The employees want more financial motivation by the company. The problem identification in the company Is there any impact between motivation towards employee’s turnover in PT. Sumatra Raya Sari Medan?” The writer will use the total population in PT. Sumatra Raya Sari Medan is 60 employees. The writer uses Arikunto Sampling theory. The sample size is 60. The writer uses census sampling technique which the writer takes all population as sample. In analyzing data, the writer used some methods such as data descriptive, the validity test, the reliability test, the correlation test, the determination test,linier regression, and the hypothesis test. According to the result calculation data through the answers of the respondents, the writer got the result of 0.92 which means motivation has a significantly strong impact towards employees’ turnover at PT. Sumatra Raya Sari Medan. From the calculation of determination test, the writer got zcount=7.07. The zcount > ztable (7.07> 1.96), This means the Null hypothesis (Ho) is rejected. The writer can conclude that motivation has impact towards employees’ turnover at PT. Sumatra Raya Sari Medan.